2020
DOI: 10.1038/s41598-020-67315-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and seasonality of major ocular trauma: a nationwide population-based study

Abstract: We designed this study to identify the epidemiological characteristics and trends of various types of ocular trauma in the population of the Republic of Korea. We conducted a nationwide, populationbased, cross-sectional study using the Korean national Health insurance claims database for January 2010 to December 2018. We compiled the monthly numbers of patients diagnosed with hyphema and those who received open reduction surgery due to orbital blowout fracture (Bof), primary closure of the cornea or sclera (pc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…When compared to OGI, visual prognosis of CGI appeared to have a better prognosis [8], [12]. This study was in agreement with the results of several other studies in terms of variations in total number of patients per year [13], seasonal variation that is influenced by different moon peaks and clusters in certain months [13], [14], higher male preponderance [6], [7], [15], [16], [17], [18], [19], predominant occurrence in productive ages [9], [20], [21], and unilaterality [16], [22], [23]. Another study reported that the most common causes of decrease in vision were penetrating injuries and intraocular foreign bodies (IOFBs) [24].…”
Section: Discussionsupporting
confidence: 90%
“…When compared to OGI, visual prognosis of CGI appeared to have a better prognosis [8], [12]. This study was in agreement with the results of several other studies in terms of variations in total number of patients per year [13], seasonal variation that is influenced by different moon peaks and clusters in certain months [13], [14], higher male preponderance [6], [7], [15], [16], [17], [18], [19], predominant occurrence in productive ages [9], [20], [21], and unilaterality [16], [22], [23]. Another study reported that the most common causes of decrease in vision were penetrating injuries and intraocular foreign bodies (IOFBs) [24].…”
Section: Discussionsupporting
confidence: 90%
“…With regards to the incidence of pathologies (Table 1), trauma-related diagnoses factors included younger age and male gender (probably due to a higher incidence of work-related minor traumas in male-dominated manual labor positions). In is interesting to note in literature that young men, mostly within the age of 20-40 years, constitute 92% to 100% of the patients presenting EEDs for intraocular foreign bodies [35,36]. The 44% decrease of traumas during the lockdown period is in accordance with other studies that reported a drop of more than 50% due to a reduction of various work-related and leisure activities dur-ing the pandemic [37,38].…”
Section: Discussionsupporting
confidence: 83%
“… 15 Furthermore, in a recent analysis using the Korean National Health Insurance claims database, an annual incidence of 1.99 per 100,000 persons for primary closure of cornea or sclera and 0.39 per 100,000 persons for intraocular foreign body (IOFB) removal were noted. 16 …”
Section: Introductionmentioning
confidence: 99%